CHARACTERISTICS CONDITION AND ENVIRONMENTAL QUALITY OF USING TRIBE SETTLEMENTS IN KEMIREN VILLAGE - Sufyan, Abu; Prajnawrdhi, Tri Anggraini; Agusintadewi, Ni Ketut (Journal of Architecture&ENVIRONMENT, 2020)
As built environment, development in Kemiren Village as traditional tourism village, community feels benefits. Those developments dynamically encourage changes, especially in characteristics and environmental quality, this cause of community space growth and some areas function. There is control to maintain characteristics of threat to change It is necessary to conduct study to identify settlement characteristics from cultural significance and environmental quality influence, which results can be utilize to make more appropriate directtion for traditional settlements preservation in Kemiren Village, which makes potential characteristics and environment feasibility as purpose to preserving community areas.Research conducted with rationalistic-qualitative, descriptive and exploratory methods, data collection techniques by field observations, interviews and documentation. Furthermore, data obtained will be map into tables, including mapping environmental conditions, characteristics, cultural meanings, and environmental quality.Based on evaluation analysis, settlements cultural significance reaches an average of 60%, with aesthetic, scarcity, and exceptional variables being elements that have high value of unique characteristics, caused by presence factor of Kemiren House, which has historical value and has potential to become cultural heritage building. Then the value of environmental quality, which is below an average of 50%, poses threat to physical formations, which can visually reduce aesthetic value and unusual environment of settlement.